Together with Time: A Material Response - Hawkhead, Mandy Kym (Curtin University, 2023)
This creative practice research project examines our relationship with time in the contemporary world. It considers how we might navigate UTC to engage with phenomenology in the present. A series of art installations draw on the profound and immersive affect of water to encourage synchronisation with temporality. This body of research speaks to ideas of authentic experience and asks one to consider how we might re-engage with materials to move affably together with time.